2024
DOI: 10.1002/chem.202304226
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Reactivities of tert‐Butyllithium by the Addition of Stoichiometric Amounts of Tetrahydrofuran

Johannes Kleinheider,
Tobias Schrimpf,
Rebecca Scheel
et al.

Abstract: In alkyllithium chemistry the highest reactivity has historically been linked to the smallest degree of aggregation possible. Since tert‐butyllithium is known to form a monomer in tetrahydrofuran solution, using just stoichiometric amounts of the lewis base to selectively form a dimeric species seemed irrational. In this study, we showed a considerable increase of the reactivity of t‐BuLi when using stoichiometric amounts of THF in the non‐polar solvent n‐pentane in order to enable the deprotonation of simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Strohmann et al reported experiments with tert -butyl lithium and THF in a ratio of 1 : 2, revealing remarkable aggregation, leading to an increase in reactivity compared to the ratios 1 : 1 and 1 : 2.5. 45 Consequently, the polymerization rate is enhanced by small amounts of THF, promoting the formation of vinylic units. The faster kinetics may also explain the broad distribution observed for entry 12.…”
Section: Resultsmentioning
confidence: 99%
“…Strohmann et al reported experiments with tert -butyl lithium and THF in a ratio of 1 : 2, revealing remarkable aggregation, leading to an increase in reactivity compared to the ratios 1 : 1 and 1 : 2.5. 45 Consequently, the polymerization rate is enhanced by small amounts of THF, promoting the formation of vinylic units. The faster kinetics may also explain the broad distribution observed for entry 12.…”
Section: Resultsmentioning
confidence: 99%